Individual blockholders and corporate risk-taking: Korean evidence - Sang-Giun Yim (Global Business & Finance Review (GBFR), 2021)
Purpose: This study examines the influence of individual blockholders on corporate risk-taking using Korean-listed firm data. Studies on corporate governance argue that non-controlling large shareholders, that is individual blockholders, increase corporate risk-taking by monitor and discipline the controlling shareholder's self-serving decisions. However, as individual blockholders have limited resources to monitor a controlling shareholder, whether individual blockholders increase corporate risk-taking is an empirical question. Design/methodology/approach: To test research the question, this study examines the influence of individual blockholders on corporate risk-taking by using multivariate regression analysis. Korean individual blockholder data are refined manually to confirm individual blockholders' independence from the controlling shareholder of the firm. Findings: The regression analysis showed that individual blockholders reduced overall corporate risk and long-term risky investments, while short-term corporate risk-taking related to credit policy increased. Besides, the persistence of risky investment decreases in the presence of individual blockholders. The empirical analysis also finds that the negative relation between individual blockholders presence and corporate risk-taking is strengthened by financial slock. These results contradict previous studies which predict that individual blockholders will increase corporate risk-taking. Research limitations/implications: This study suggests that individual blockholders avoid corporate risk-taking if they have insufficient resources to discipline a controlling shareholder. The results of this study highlight that institutional support is necessary for individual blockholders to perform the corporate governance role, which is applicable for all countries that the concentrated ownership prevails. Originality/value: Using manually collected data, this study reports the empirical results that contradict the expectation of most prior studies on the influence of individual shareholders on corporate risk-taking.
Keywords: 650; Individual blockholder; Controlling shareholder; Corporate governance; Corporate risk-taking; Risky investment